Ultrastructure of precapillary sphincters and the neurovascular unit - Søren Grubb (Vascular Biology, 2023)
Neurons communicate with vasculature to regulate blood flow in the brain, a process maintained by the neurovascular unit (NVU). This interaction, termed neurovascular coupling, is believed to involve astrocytes or molecules capable of traversing the astrocytic endfeet. The precise mechanism, however, remains elusive. Using large 3D electron microscopy datasets, we can now study the entire NVU in context of vascular hierarchy. This study presents evidence supporting the role of precapillary sphincters as a nexus for neurovascular coupling and endothelial transcytosis. It also highlights the role of fibroblast-synthesized collagen in fortifying first-order capillaries. Furthermore, I demonstrate how astrocytic endfeet establish a barrier for fluid flow and reveal that the cortex’s microvasculature is semicircled by an unexpected arrangement of parenchymal neuronal processes around penetrating arterioles and arterial-end capillaries in both mouse and human brains. These discoveries offer insights into the NVU’s structure and its operational mechanisms, potentially aiding researchers in devising new strategies for preserving cognitive function and promoting healthy aging.